2019
DOI: 10.1016/j.vaccine.2019.03.003
|View full text |Cite
|
Sign up to set email alerts
|

It’s not all about autism: The emerging landscape of anti-vaccination sentiment on Facebook

Abstract: Background: Due in part to declining vaccination rates, in 2018 over 20 states reported at least one case of measles, and over 40,000 cases have been confirmed in Europe. Antivaccine posts on social media may be facilitating anti-vaccination behaviour. This study aimed to systematically characterize (1) individuals known to publicly post antivaccination content on Facebook, (2) the information they convey, and (3) the spread of this content. Methods: Our data set consisted of 197 individuals who posted anti-va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
114
0
8

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 184 publications
(125 citation statements)
references
References 37 publications
(51 reference statements)
3
114
0
8
Order By: Relevance
“…The finding in H&C's Table 9 of "Reports of desired retribution against physicians performing non-therapeutic circumcision" is consistent with similar sentiments, and threats, expressed on social media, as revealed in a recent study of Facebook comments by anti-vaccination proponents, who were found to be more likely to be anti-MC and anti-water fluoridation [163]. The anti-MC and anti-vaccination movements share similar features: casting doubt on the validity of the scientific method, employment of anecdotes and "junk science," demonizing anyone who dares disagree with their beliefs, and resorting to specious arguments and twisted logic.…”
Section: Threats and Retributionsupporting
confidence: 77%
“…The finding in H&C's Table 9 of "Reports of desired retribution against physicians performing non-therapeutic circumcision" is consistent with similar sentiments, and threats, expressed on social media, as revealed in a recent study of Facebook comments by anti-vaccination proponents, who were found to be more likely to be anti-MC and anti-water fluoridation [163]. The anti-MC and anti-vaccination movements share similar features: casting doubt on the validity of the scientific method, employment of anecdotes and "junk science," demonizing anyone who dares disagree with their beliefs, and resorting to specious arguments and twisted logic.…”
Section: Threats and Retributionsupporting
confidence: 77%
“…For "anti-vax" and "vaccine sceptic" the vaccine safety is the topic most discussed when doubts about vaccination strategies are proposed. 6 Although international guidelines recommended that all adverse events must be detected and reported to improve product safety and management, the passive surveillance system adopted by national authorities is affected by an high risk of AEFIs underreporting, especially for not serious events. 7 For this reason, recently active surveillance and supplemental strategies are being incorporated into vaccine safety programs: these include active screening for targeted conditions of interest (e.g., hospitalization), monitoring of new data sources and real-time methodologies to detect changes in vaccine safety data in these sources.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, it is not uncommon for people to dismiss entirely a doctor's advice based on conflicting advice online; as two examples, consider the anti-vaccination movement (Brownlie & Howson, 2005) as well as the use of crowdsourced medical information sites (Bakke, 2015). A key strategy of this movement is to incite distrust in the traditional medical community through proliferation of personal stories and conspiracy theories, websites devoted to "alternative" interpretations of scientific data, and the promotion of alternative treatments, medications, and educational materials (Hoffman et al, 2019;Yiannakoulias et al, 2019). An accompanying strategy is the (mis)use of crowdsourced review forums, such as Yelp, with coordinated activities of posting negative reviews of doctors and medical institutions assessed as "pro-vaccine. "…”
Section: Collective Online Social Actionmentioning
confidence: 99%